Upaya Peningkatan Kemampuan Membaca Al-Qur’an Santri Melalui Metode Tilawati Di TPA Babul Khoir - Luluk Nur Indah Sari; Faelasuf Faelasuf (CV. ULIL ALBAB CORP, 2024)
This study examines the effectiveness of the Tilawati method in improving the ability to read the Qur'an of students at Babul Khoir TPA, Kombeng Indah Village. The Qur'an is the holy book of Muslims that was revealed to the Prophet Muhammad SAW and maintained its purity by Allah SWT. Despite its importance, many Muslims have difficulty reading the Qur'an correctly due to ineffective understanding and learning methods. The Tilawati method, which emphasizes comfort and pleasure in learning, was used to address this issue. The research used a descriptive qualitative method with a case study, involving participatory observation, in-depth interviews, and documentation. The research subjects were ustadz and santri of Babul Khoir TPA. The results show that the Tilawati method improves the santri's understanding of the reading structure, adherence to tajweed, and pronunciation of hijaiyah letters. Santri became more proficient and fluent in reading the Qur'an. The research emphasizes the importance of teacher certification and training as well as structured, high-quality teaching. The Tilawati method not only improves Qur'an reading skills but also makes learning fun. These results support the use of the Tilawati method as an effective strategy in Qur'ānic education in various Islamic educational settings.